Kidney and urogenital abnormalities in Down syndrome: a meta-analysis - Caterina Maria Rossetti; Giacomo D. Simonetti; Mario G. Bianchetti; Sebastiano A. G. Lava; Giorgio Treglia; Carlo Agostoni; Gregorio P. Milani; J. Peter de Winter (Italian Journal of Pediatrics, 2024)
Abstract Background Reviews on Down syndrome do not or only marginally address the issue of kidney and urogenital tract abnormalities, and lower urinary tract dysfunctions. Hence, we performed a meta-analysis of the literature.  Methods A literature search was undertaken in the Library of Medicine, Web of Science and Excerpta Medica. The search algorithm combined various keywords: (Down syndrome OR trisomy 21 OR mongolism) AND (kidney OR urinary tract OR bladder) AND (malformation OR dysfunction OR anomaly OR abnormality OR size). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement was used. Results Eight case-control studies were retained for the final analysis. Three studies addressed the prevalence of kidney and urogenital tract abnormalities: an increased pooled relative risk of 5.49 (95%-CI: 1.78–16.93) was observed in Down syndrome. Penile malformations, obstructive malformations (including urethral valves), dilated urinary tract system, and kidney hypodysplasia were especially common. Three reports addressed the prevalence of lower urinary tract dysfunction: an increased pooled relative risk of 2.95 (95%-CI: 1.15–7.56) was observed. Finally, an autoptic study and an ultrasound study disclosed a reduced kidney size in Down syndrome. Conclusions This meta-analysis indicates that abnormalities of the kidney and urogenital tract, lower urinary tract dysfunctions, and a reduced kidney size present with an increased frequency in individuals with Down syndrome.